PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH KONFLIK PERAN DAN STRES KERJA TERHADAP INTENSI KELUAR (STUDI PADA ANANTARA SEMINYAK RESORT & SPA, BALI) - Novie Margarani Akwan; Ni Wayan Sri Suprapti; Desak Ketut Sintaasih (STIE Mandala Jember, 2016)
Intention to leave is an important issue that needs attention for management especially in the hospitality industry. Intention to leave is an indicatication from the actual turnover, and high turnover numbers can caused significant losses for the company. The aim of this study is to analyze the role of job satisfaction in mediating the effects of role conflict and job stress to the intention of leave. The study is conducted at Anantara Seminyak Resort & Spa, Bali with a sample of 60 employees who were taken from a population of 148 people using Slovin method. Collecting data using questionnaire and data analysis techniques with PLS. The results showed that the role conflict and job stress has negative and significant effect to employee job satisfaction. Role conflict and job stress has positive and significant effect to the intention to leave. Job satisfaction has negative and significant effect to the intention to leave. Job satisfaction proved to be partially mediation in relations of role conflict and job stress to the employee intention to levae. Implications of this study is to suppress intention to leave and prevent the occurrence of actual turnover, is important for the management of the company to make efforts that can reduce role conflict and job stress of the employees.